Online assessment of the electric locomotive life cycle cost - A. A. Akishin; V. V. Brekson; O. V. Vinogradova; V. A. Kuchumov; N. D. Mironov; N. B. Nikiforova (Вестник Научно-исследовательского института железнодорожного транспорта, 2019)
The selection and supply of electric locomotives based on the life cycle contract requires a more thorough review of indicators of their effectiveness implemented in operation. This study examines the main operation indicators currently used: coefficients of operational availability, technical availability, intrinsic availability (instantaneous), availability of the locomotive fleet, performed ton-kilometer operation, and electric power consumption. However, these indicators are not comprehensive and do not provide an overall economic assessment of operation. For a comprehensive assessment of the effectiveness of operation of locomotives, an online calculation of the life cycle cost is proposed. This involves directly using operating and service data for its performance, and the calculation of an indicator — life cycle specific cost (LCSC). The online LCSC is a uniform criterion associated with the energy efficiency of the performed transportation, volume of the ton-kilometer operation, operation expenses, reliability of electric locomotive, and its equipment availability ratio (EAR). The LCSC analysis enables assessment of deviations of the operation effectiveness indicators from those planned, and determining a strategy for improvement of the electric locomotive. It helps to define peculiarities in the operation of an electric locomotive and to forecast its condition and potential properties. Additionally, the LCSC facilitates analyzing the condition of a group of electric locomotives when changing the operation technology (for example, operation starting with increased rolling stock weight), including assessment of the extent of economic benefits of fulfilled measures.Currently, scientists of the JSC “VNIIZhT” and specialists of LLC “Ural Locomotives” are conducting tests on the electric locomotives 2EC6 on the Oktyabrskaya railroad using the “Online LCC” server. This allows online analysis of information collected on the operation and servicing of locomotives under the life cycle contract, pro viding effective and prompt control of the electric locomotive fleet.